Dissecting pathways of cancer-associated cachexia and its evidence-based relation to vitamin D - Nurul Ratna Manikam; Andrijono; Fariz Nurwidya; Fiastuti Witjaksono; Isabela Andhika Paramita (Indonesian Nutrition Association, 2026)
Introduction: Cancer-associated cachexia (CAC) is a complex metabolic syndrome. It affects 0,5-1% of the general population and 60-83% of cancer patients. Vitamin D has a potential immunological role in cancer cachexia. However, the mechanism remains unclear. Method: This review outlines the complex mechanisms of CAC, a metabolic syndrome marked by muscle loss affecting 80% of cancer patients and the potential action of vitamin D. We highlight the limited studies exploring vitamin D’s impact on CAC, based on cachexia parameters. Result: The Warburg effects in CAC are understood to involve elevated energy use, driven by the tumor microenvironment (TME) and pro-inflammatory cytokines. This present review explores the mechanism of cachexia on skeletal, adipose tissue, liver and tumor microenvironment. At the same time vitamin D deficiency in cancer correlates with poor prognosis due to its critical role in immune modulation. Notably, various clinical trials showed the beneficial roles of vitamin D in reducing inflammation, pain and increasing weight. Conclusion: Few studies had explored the beneficial effects of vitamin D in cancer; However, limited evidence exists on immunomodulatory effects of vitamin D. This critical gaps stressing the need for further clinical research across various cancer types.